A realist review of shared medical appointments: How, for whom, and under what circumstances do they work?. Issue 1 (December 2017) - Kirsh, Susan; Aron, David; Johnson, Kimberly; Santurri, Laura; Stevenson, Lauren; Jones, Katherine; Jagosh, Justin
Abstract Background Shared medical appointments (SMAs) are doctor-patient visits in which groups of patients are seen by one or more health care providers in a concurrent session. There is a growing interest in understanding the potential benefits of SMAs in various contexts to improve clinical outcomes and reduce healthcare costs. This study builds upon the existing evidence base that suggests SMAs are indeed effective. In this study, we explored how they are effective in terms of the underlying mechanisms of action and under what circumstances. Methods Realist review methodology was used to synthesize the literature on SMAs, which included a broad search of 800+ published articles. 71 high quality primary research articles were retained to build a conceptual model of SMAs and 20 of those were selected for an in depth analysis using realist methodology (i.e., middle-range theories and and context-mechanism-outcome configurations). Results Nine main mechanisms that serve to explain how SMAs work were theorized from the data immersion process and configured in a series of context-mechanism-outcome configurations (CMOs). These are: (1) Group exposure in SMAs combats isolation, which in turn helps to remove doubts about one's ability to manage illness; (2) Patients learn about disease self-management vicariously by witnessing others' illness experiences; (3) Patients feel inspired by seeing others who are coping well; (4) Group dynamics lead patients and providers to developing more equitable relationships; (5) Providers feel increased appreciation and rapport toward colleagues leading to increased efficiency; (6) Providers learn from the patients how better to meet their patients' needs; (7) Adequate time allotment of the SMA leads patients to feel supported; (8) Patients receive professional expertise from the provider in combination with first-hand information from peers, resulting in more robust health knowledge; and (9) Patients have the opportunity to see how the physicians interact with fellow patients, which allows them to get to know the physician and better determine their level of trust. Conclusions Nine overarching mechanisms were configured in CMO configurations and discussed as a set of complementary middle-range programme theories to explain how SMAs work. It is anticipated that this innovative work in theorizing SMAs using realist review methodology will provide policy makers and SMA program planners adequate conceptual grounding to design contextually sensitive SMA programs in a wide variety of settings and advance an SMA research agenda for varied contexts.